2021
DOI: 10.7196/sajch.2021.v15i1.01775
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric out-of-theatre procedural sedation at a tertiary children’s hospital: A prospective observational study

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.Procedural sedation and analgesia (PSA) describes the use of agents, such as sedatives and analgesics, to alleviate anxiety, pain and fear during diagnostic and therapeutic procedures. [1] The South African Society for Anaesthesiologists (SASA) defines the goals of procedural sedation as reducing the patient's fear, anxiety and distress while minimising physical discomfort, pain and psychological trauma, maintaining control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some of the most precious resources are time, beds, space, and the specialists available. It is therefore essential to provide PSA safely to the paediatric patient outside of theatre [ 1 , 2 , 4 ]. Applying evidence-based medicine and newly developed guidelines can provide PSA safely with minimal delays and thus save time, money, and other resources [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most precious resources are time, beds, space, and the specialists available. It is therefore essential to provide PSA safely to the paediatric patient outside of theatre [ 1 , 2 , 4 ]. Applying evidence-based medicine and newly developed guidelines can provide PSA safely with minimal delays and thus save time, money, and other resources [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Red Cross War Memorial Children`s Hospital (RCWMCH) is the largest paediatric hospital in Africa and is situated in Cape Town. The hospital identified the need for an out-of-theatre sedation service due to the increased need for PSA [ 4 ]. They did an observational study in 2019 with the primary aim of defining the number of cases of PSA performed outside of operating theatre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently limited information on procedural sedation practices in LMICs, with published research on pediatric procedural sedation in Africa almost non-existent. A recent prospective observational study at Red Cross War Memorial Children's Hospital in Cape Town, South Africa reported performing ∼200 pediatric procedural sedations per month [12] . However, the study was limited to one city in one country, at one of the largest children's hospitals in Africa.…”
Section: Introductionmentioning
confidence: 99%